Data from: Regional response of grassland productivity to changing environment conditions influenced by limiting factors - He, Nianpeng (Dryad, 2020)
Regional differences and regulatory mechanisms of vegetation productivity
response to changing environmental conditions constitute a core issue in
macroecological researches. To verify the main limiting factors of
different macrosystems [temperature-limited Tibetan Plateau (TP),
precipitation-limited Mongolian Plateau (MP), and nutrient-limited Loess
Plateau (LP)], we conducted a comparative survey of the east-west
grassland transects on the three plateaus and explored the factors
limiting regional productivity and their underlying mechanisms. The
results showed that aboveground net primary productivity (ANPP) of LP
(109.10 ± 16.76 g m−2 yr−1) was significantly higher than that of MP
(66.71 ± 11.11 g m−2 yr−1) and TP (57.02 ± 10.59 g m−2 yr−1). The response
rate of ANPP with environmental changes was different among different
plateaus, being closely related to the main limiting factors. On MP, this
was precipitation, on LP it was temperature and nutrients, and on TP, it
was non-specific, reflecting restriction by the extremely low temperature.
After autocorrelation screening of environmental factors, different
regions exhibited different productivity response mechanisms. MP was
mainly influenced by temperature and precipitation, LP was influenced by
temperature and nutrient, and TP was influenced by nutrient, reflecting
the modifying effect of the main limiting factors. The effect of each
regional environment on ANPP was 72.56% on average and only 27.18% after
simple regional integration. The regional model could optimize the
simulation error of the integrated model, and the relative deviations in
MP, LP, and TP were reduced by 31.76%, 17.22%, and 2.23%, respectively.
These findings indicate that the grasslands on the three plateaus may have
different or even the opposite mechanisms to control productivity.
Field investigation in 2018
Keywords: FOS: Earth and related environmental sciences